Hard X‐ray full‐field nanoimaging using a direct photon‐counting detector. (1st February 2023) - Flenner, Silja; Hagemann, Johannes; Wittwer, Felix; Longo, Elena; Kubec, Adam; Rothkirch, André; David, Christian; Müller, Martin; Greving, Imke
Abstract : A direct photon‐counting detector was used for different nanoimaging phase contrast techniques, increasing the temporal resolution. Abstract : Full‐field X‐ray nanoimaging is a widely used tool in a broad range of scientific areas. In particular, for low‐absorbing biological or medical samples, phase contrast methods have to be considered. Three well established phase contrast methods at the nanoscale are transmission X‐ray microscopy with Zernike phase contrast, near‐field holography and near‐field ptychography. The high spatial resolution, however, often comes with the drawback of a lower signal‐to‐noise ratio and significantly longer scan times, compared with microimaging. In order to tackle these challenges a single‐photon‐counting detector has been implemented at the nanoimaging endstation of the beamline P05 at PETRA III (DESY, Hamburg) operated by Helmholtz‐Zentrum Hereon. Thanks to the long sample‐to‐detector distance available, spatial resolutions of below 100 nm were reached in all three presented nanoimaging techniques. This work shows that a single‐photon‐counting detector in combination with a long sample‐to‐detector distance allows one to increase the time resolution for in situ nanoimaging, while keeping a high signal‐to‐noise level.